Aggregation is impaired in starved platelets due to enhanced autophagy and cellular energy depletion. (19th May 2019) - Paul, Manoj; Hemshekhar, Mahadevappa; Kemparaju, Kempaiah; Girish, Kesturu S.
Abstract: Platelet hyperactivity is the hallmark of thrombosis and hemostasis disorders including atherosclerosis, diabetes, stroke, arthritis, and cancer causing significant mortality and morbidity. Therefore, regulating platelet hyperactivity is an ever growing interest. Very recently, basal autophagic process has been demonstrated to be essential for normal functioning of platelets. However, autophagy can be elevated above basal level under conditions like starvation, and how platelets respond in these settings remains to be elucidative. Therefore, in this study we demonstrate a substantial autophagy induction (above basal level) by starvation, which decreases platelet aggregation responses to various agonists. The decreased aggregation in starved platelets was restored in combination with autophagy inhibitors (3-methyladenine and NH4 Cl) and acetate supplementation. Starved platelets also showed decreased calcium mobilization, granule release, and adhesive properties. Furthermore, ex vivo platelets obtained from starved rats showed increased autophagy markers and decreased aggregation responses to various agonists. Our results distinctly explain that enhanced autophagy and cellular energy depletion are the cause for decreased platelet activation and aggregation. The study emphasizes the cardinal role of starvation and autophagy in the management of diseases and disorders associated with platelet hyperactivity.